Putting information first Luciano Floridi and the philosophy of information - Allo, Patrick (Metaphilosophy, 2010)
Putting Information First focuses on Luciano Floridi's contributions to the philosophy of information. Respected scholars stimulate the debate on the most distinctive and controversial views he defended, and present the philosophy of information as a specific way of doing philosophy. Contains eight essays by leading scholars, a reply by Luciano Floridi, and an epilogue by Terrell W. Bynum. Explains the importance of philosophy of information as a specific way of doing philosophy. Focuses directly on the work of Luciano Floridi in the area of philosophy of information, but also connects to contemporary concerns in philosophy more generally. Illustrates several debates that arise from core themes in the philosophy of information."-- Provided by publisher.